MARKET DEVELOPMENT STRATEGY TO INCREASE MARKET SHARE WITH THE DIGITAL MARKETING REVOLUTION - Titin Titin; Luluk Nur Azizah; Najah Rifat Mahiroh (DIA: Jurnal Administrasi Publik, 2022)
This market development strategy is one part of the company's various strategies to achieve growth in an effort to increase market share. The company opens new markets to market products so that the products are better known and liked by the wider community. Changes in communication technology which is a way or tool for people to interact, then the digital marketing revolution is very influential on changes in consumer behavior which will have an impact on market development. This research uses descriptive qualitative research. The research subjects consisted of 10 Micro, Small and Medium Enterprises with a declining number of product sales. The technique of collecting data is triangulation (combined) and the results of qualitative research emphasize meaning rather than generalization. The results of this study are SMEs in Lamongan Regency practice digital marketing strategies (digital marketing) online through social media such as Facebook, Instragram, and other internet networks, all of which are connected to a wider reach of consumers. MSMEs in Lamongan Regency cooperate with the POL (Lamongan Online Market) which was initiated by Perumda Pasar Kabupataen Lamongan, a market place selling online media that can be accessed easily. And the application of digital marketing carried out by MSMEs in Lamongan Regency can increase sales. It can be seen based on the SWOT analysis, MSMEs in Lamongan Regency are in the right and relevant position, namely in quadrant I (growth) in the application of digital marketing.